The Life Cycle, Aging, and Death: Dialectical Perspectives - Datan, Nancy; Sardello, Robert J.; Marnocha, Mark; Rappoport, Leon; Cohler, Bertram J. (Human development, 1977)
The life cycle and its study are seen as the locus of dialectical intersections through the several perspectives of the contributors to this symposium. Sardello and Datan locate the dialectic of the life cycle at the interface between youth and age: Sardello proposes that the polarities of youth and age are united in the individual's dialectical consciousness of the life cycle, while Datan argues that the narcissism of the life cycle, binding the individual in temporal constraints, acts as a barrier to this unity, and that narcissism is an element in the intrapsychic origins of generational conflict. Rappoport places the dialectic of the life cycle at the interface between the individual life cycle and its social context, noting that the unity between youth and age is a consequence of the passivity imposed upon both. Marnocha sees the dialectical focus at the interface between subject and experimenter, suggesting that both must face their personal confrontation with death together in order to achieve a meaningful psychology of death. Cohler sees this dialectic as one example of the broader issue of the denial of subjective knowledge in the pursuit of objective knowledge, arguing for a dialectical synthesis of personal involvement and scientific investigation as particularly valuable in the study of the life cycle, aging, and death.